Bone fractures: assessment and management. (29th February 2016) - Lim, L; Sirichai, P
Abstract: Severe dental traumatic injuries often involve the supporting bone and soft tissues. This article outlines the current concepts in the management of dentoalveolar fractures for the general dental practitioner with case reports to illustrate management principles and techniques.